Epidemiological and Diagnostic Study for Fasciola gigantica in Buffaloes by using PCR Technique at Thi-Qar Province - العبادي, فاضل عباس (University of Thi-Qar Journal of Science, 2014)
The present study includes epidemiological survey for giant liver fluke parasite Fasciola gigantica in immolated buffaloes in slaughter house of Nasirriya city in Thi-Qar Province. The period of study extends from the beginning August 2008 up to end of July 2009. A total of 323 buffaloes were examined with percentage of whole infection 142(43.96%) and intensity of whole infection 17.5. The highest percentage for whole infection in buffaloes is in November 71.43 % and the least one is recorded in August 23.53 %, while the highest intensity of infection is recorded in April 47.91 and their least was in August 5.25 and the significant difference (P<0.01) is found in percentage and intensity of infection in buffaloes during the month of the year. The rate of liver infection percentage in buffaloes 43.96 % is higher than rate of gallbladder infection percentage 7.12 % in all the months of the year. Significant differences are observed in the percentage of infection in both liver and gallbladder during the months of the year (P<0.01). The infection intensity of liver in buffaloes is higher from gallbladder infection intensity in all months of the year with significant differences (P<0.01) except April and May.The age has an influence on thepercentage and intensity of infection in buffaloes.